Pengaruh suplementasi Zn terhadap perubahan indeks TB/U anak stunted usia 24-36 bulan - Kusudaryati, Dewi Pertiwi Dyah; Muis, Siti Fatimah; Widajanti, Laksmi (Jurnal Gizi Indonesia (The Indonesian Journal of Nutrition), 2017)
Background : Zn supplementation on stunted children in multiple research get the result inconsistent concerning the effect of Zn on children’s growth.Objective : To examine the effect of Zn supplementation to the change in height for index among stunted children age between 24-36 months.Methods: The research design is randomized pretest posttest control group design. The total of thirty six stunted children are divided into two groups. The treatment group is received syrup with 20 mg ZnSO4 twice a week for three months. The control group received placebo without Zn. Height for age z score (HAZ) on WHO Child Growth 2006 is used to measure height for age index while dietary intake and infection diseases are used as confounding variables.Result : There is significant difference in HAZ before and after supplementation at treatment group (p<0.001) and control group (p<0.001). There is a significant difference of the change in HAZ between the treatment group and control group (p=0.006). Percentage Achievement of Energy, Protein, and Zn Dietary Allowance have significant difference between the treatment group and control group (p=0.009; p<0.001; p<0.001, respectively). The change in HAZ, Percentage Achievement of Energy, Protein, and Zn Dietary Allowance are higher in treatment group than control group. Duration of diarrhea (p=0.045) and morbidity (p=0.019) are lower in treatment group than control group. Conclusion : Zn Supplementation among stunted children have significant effect on the change in HAZ, dietary intake, and infection.